Long‐term minnow community trait shifts and metacommunity dynamics in a geomorphically unstable river. Issue 4 (22nd April 2022) - Stearman, Loren W.; Schaefer, Jacob F.
Abstract: Ecological disturbances may affect both habitat connectivity and heterogeneity, changing the dominant metacommunity processes affecting local communities. Altered fluvial sediment dynamics in rivers experiencing headcutting and accelerated erosion may foster morphologically unstable reaches in which supplies of habitat‐forming materials are spatially and temporally unpredictable. We hypothesise such environments will select for species with traits which promote dispersal or rapid resource use. We tested this hypothesis using historical and recent datasets from a biologically and functionally diverse taxonomical group, minnows (Leuciscidae and Cyprinidae) in the Bayou Pierre, Mississippi. Local communities decreased in both α and β‐diversity over time. Spatial autocorrelation of communities was consistently high through time, and more strongly related to regional community structure than local habitat variables in contemporary data. Communities shifted towards species with larger body sizes, less parental care, shorter age at maturity and higher fecundity. Communities also shifted towards more generalist species with lower potential trophic positions, and keystone species declined. Our data support the hypothesis of community‐level shifts towards species with dispersal trait syndromes and opportunistic resource utilisation. These shifts have led to a decrease in ecological complexity and overall homogenisation of minnow communities in the geomorphically evolving Bayou Pierre mainstem. The Bayou Pierre presents a unique window into ecological dynamics in a watershed characterised by altered sediment dynamics and sediment loss, in contrast to the large body of literature examining systems with increased sedimentation. These insights demonstrate the importance of studying the full range of fluvial sediment dynamics, including how broader processes of loss and transport may affect long‐term habitat stability, persistent trait syndromes and metacommunity dynamics.